Perbedaan Geomorfologi Lahan Desa Rempek dan Desa Pusuk Tanjung Kabupaten Lombok Utara, Nusa Tenggara Barat - Salwa, Hanna; Jayawangsa, Rahman; Parwati, Galuh; Ashari, Rowi; Andriyani Lestariningsih, Wiwid; Larasati, Chandrika Eka (Jurnal Ilmu Kelautan Lesser Sunda, 2025)
There are two villages in North Lombok Regency, namely Rempek Village and Tanjung Village which have many clusters of hills which are usually connecting routes between districts, namely West Lombok Regency and North Lombok Regency. This study aims to determine the differences in land forms in two villages, namely Pusuk Tanjung Village and Rempek Village, North Lombok Regency. The data identified the geomorphology of the landform using remote sensing, digital elevation models (DEM), and interview observation data. It is known that the slope in the Rempek Village area has a slope that varies with lowland formations, highlands, and there are low hills, steep hills, and mountains. which has hilly areas with the potential for landslides caused by porous soil structures and Pusuk Tanjung Village with land formations. lowlands, mountains, low hills, and high hills and steep hills that have the potential for landslides which are influenced by human activities (anthropogenic) due to dredging of hills which are used as road access.